Influence of HLA-C environment on the spontaneous clearance of hepatitis C in European HIV–HCV co-infected individuals. (2nd February 2021) - Legrand, N; David, G; Rodallec, A; Gaultier, A; Salmon, D; Cesbron, A; Wittkop, L; Raffi, F; Gendzekhadze, K; Retière, C; Allavena, C; Gagne, K
Summary: Natural killer (NK) cell functions are regulated by diverse inhibitory and activating receptors, including killer cell immunoglobulin-like receptors (KIR), which interact with human leukocyte antigen (HLA) class I molecules. Some KIR/HLA genetic combinations were reported associated with spontaneous clearance (SC) of hepatitis C virus (HCV) but with discordant results, possibly reflecting KIR and/or HLA gene polymorphism according to populations. KIR/HLA genetic combinations associated with both an exhaustive NK and T cell repertoire were investigated in a cohort of HIV–HCV co-infected individuals with either SC ( n = 68) or chronic infection (CI, n = 163) compared to uninfected blood donors [controls (Ctrl), n = 100]. Multivariate analysis showed that the HLA C2C2 environment was associated with SC only in European HIV–HCV co-infected individuals [odds ratio (OR) = 4·30, 95% confidence interval = 1·57–12·25, P = 0·005]. KIR2D + NK cell repertoire and potential of degranulation of KIR2DL1/S1 + NK cells were similar in the SC European cohort compared to uninfected individuals. In contrast, decreased frequencies of KIR2DS1 + and KIR2DL2 + NK cells were detected in the CI group of Europeans compared to SC and a decreased frequency of KIR2DL1/S1 + NK cells compared to controls. Regarding T cells, higher frequencies of DNAX accessory molecule-1 (DNAM-1) + and CD57 + T cells were observed in SC in comparison to controls. Interestingly, SC subjects emphasized increased frequencies of KIR2DL2/L3/S2 + T cells compared to CI subjects. Our study underlines that the C2 environment may activate efficient KIR2DL1 + NK cells in a viral context and maintain a KIR2DL2/L3/S2 + mature T cell response in the absence of KIR2DL2 engagement with its cognate ligands in SC group of HCV–HIV co-infected European patients. Graphical Abstract: